Metodologické zásady - Effenberger, Vratislav (Filosoﬁcký časopis)
This study dating from the early 1970s is an attempt by the author, Vratislav Effenberger, to summarize the fundamental principles and categories of the theoretical system he had been developing since approximately the mid-1960s, and which he himself referred to as the “phenomenology of imagination”. The aim of this philosophical project was to enable the conceptualization and examination of the surrealistically conceived imagination as a means for the ideological understanding of reality and of exerting influence on it. In the study, Effenberger gives a brief sketch of his original conceptual apparatus (mental morphology, psychoideology, idea models, ideological dominants, regulating lines, etc.), points to some of the inspirational sources of his thinking (Max Dvořák, F. X. Šalda, Karel Teige, Roman Jakobson) and presents the outlines of his critique of contemporary culture and society.